2010
DOI: 10.1186/1423-0127-17-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of taurine in heart and muscle

Abstract: Taurine (aminoethane sulfonic acid) is an ubiquitous compound, found in very high concentrations in heart and muscle. Although taurine is classified as an amino acid, it does not participate in peptide bond formation. Nonetheless, the amino group of taurine is involved in a number of important conjugation reactions as well as in the scavenging of hypochlorous acid. Because taurine is a fairly inert compound, it is an ideal modulator of basic processes, such as osmotic pressure, cation homeostasis, enzyme activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
197
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(231 citation statements)
references
References 82 publications
10
197
0
4
Order By: Relevance
“…35) Furthermore, a hypertrophic stimulus, angiotensin II, was also found to promote apoptosis of cardiac myocytes 36) and Tau could reduce the angiotensin II-mediated oxidative stress. 37) Consistently, we found that taurine protected cardiomyocytes against apoptosis induced by H2O2. Taurine enhanced the SOD concentration and inhibited MDA production to a greater extent than did the cells in the H2O2 group.…”
Section: Discussionsupporting
confidence: 75%
“…35) Furthermore, a hypertrophic stimulus, angiotensin II, was also found to promote apoptosis of cardiac myocytes 36) and Tau could reduce the angiotensin II-mediated oxidative stress. 37) Consistently, we found that taurine protected cardiomyocytes against apoptosis induced by H2O2. Taurine enhanced the SOD concentration and inhibited MDA production to a greater extent than did the cells in the H2O2 group.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, taurine deficiency is associated with various pathologies including heart dysfunction [31], abnormalities of brain development [32], and cardiomyopathy [33]. In the astrocytes and the neurons, taurine is the principal osmolyte which during hypotonic or hypertonic conditions it goes out from or accumulates inside the cell, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
“…This effect of taurine-caffeine 374 combined was not transferable to skeletal muscle in the present study when used at a physiological 375 level (70µM human maximal) of caffeine concentration and the combined effect was not greater 376 than that of caffeine alone in the present study. Besides the differences in caffeine concentration, 377 10mM caffeine would be highly toxic for human consumption (Fredholm et al 1999), it is considered 378 that the effects of taurine are more profound in heart tissue which may further contribute to the 379 differences in results (Schaffer et al 2010). 380…”
Section: The Effect Of Physiological Concentrations Of Taurine and Camentioning
confidence: 99%